Predictors of Change of Working Alliance Over the Course of Probation Supervision: a Prospective Cohort Study - Sturm, Annelies (International journal of offender therapy and comparative criminology, 2020)
The body of evidence that the working alliance is associated with positive outcomes for mandated clients is growing. The aim of this research was to investigate the influence of several characteristics of probation officers (POs) and offenders on the course of the working alliance during probation supervision. This study examined the patterns on the four alliance subscales: Trust, Bond, Goals-Restrictions, and Reactance of the Working Alliance With Mandated Clients Inventory (WAMCI) in 201 offenders and their 137 POs. Three patterns on each alliance subscale were found: deteriorating, improving, and stable. Multinomial logistic analysis revealed that change of POs and the preference of the PO to maintain rules were associated with a deteriorating Trust pattern. From the perspective of the offenders, being motivated to take part in supervision was associated with a stable pattern on every alliance subscale, but having problems with substance use increased the likelihood of a deteriorating pattern on every alliance subscale.